Language Analysis of BTS’ Digital Marketing Strategies - Salsadila Sindya Dewantari; Noverita Wahyuningsih (UPT P2M Politeknik Negeri Malang, 2024)
This study analyzes the language used in BTS' digital marketing strategies, specifically in their social media posts and advertisements. A corpus of 120 social media posts and advertisements was compiled. A qualitative method was used to examine language use. In addition, the theory that is used is a theory from Martin Joos. Results show that BTS' digital marketing strategies utilize a range of linguistic devices and digital marketing strategies to connect with their audience and promote their brand. Additionally, the study identified patterns of language between Instagram and Twitter platforms. This study also provides insights into the language strategies used by BTS in their digital marketing, which can inform the development of effective digital marketing strategies for other brands targeting similar audiences. As a result, the researchers found that the most used language style in BTS' digital marketing strategies is the consultative style, which accounted for 62.5% of the analyzed posts. The company utilizes this style to provide advice, product information, and promote events, aiming to establish a helpful and trustworthy relationship with their audience. Additionally, the casual language style was observed in 37.5% of the posts, creating a friendly and approachable tone that resonates with BTS' youthful image.